Effect of air pressure on gas transport properties and physical aging of poly(phenyleneoxide) (PPO) membranes - Alsari, Alsdeg Mohamad (University of Ottawa (Canada), 2008)
The objective of this research work is to understand the molecular mechanism involved in physical aging of amorphous glassy polymers. Free volume and segmental mobility arguments are commonly used to explain both the gas transport process and the physical aging of glassy polymers. Hence, gas permeation through glassy polymeric membranes is considered as an attractive tool to detect any time dependent changes of polymer free volume. Especially, emphasis is placed, in this work, on determining whether or not an experimental routine affects the time dependent changes of glassy polymeric membranes. In the first part (Chapter 5), permeability data of oxygen and nitrogen were obtained from air permeation experiments under different pressures using dense polyphenylene oxide (PPO) membranes of different thicknesses, after the membranes were almost fully stabilized. Opposite trends were observed with respect to oxygen and nitrogen as their permeabilities changed with changes in feed pressure and membrane thickness. Moreover, the pressure effect on oxygen permeability was reversed when the membrane was flipped upside down. Attempts were made to interpret the above experimental observations within a framework of entropy and enthalpy effect on the energy barrier for gas permeation and the change in void space in the cross-sectional direction of a dense PPO membrane. In the second part (Chapter 6), resemblance of aging curves of gas separation membranes to visco-elastic response curves was observed for all the studied membranes. Membrane aging curves consist of elastic and viscous components. It was further concluded that the elastic component of polymer relaxation was enhanced when membranes were aged at lower pressures while the viscous component was enhanced at higher gas pressures. The transition from the elasticity dominant to the viscosity dominant region occurred more quickly for thicker membranes. In the third part (Chapter 7), the effect of gas pressure on membrane aging was studied thoroughly by applying feed gas pressure continuously or by reducing the feed gas pressure intermittently. The effect of pressure on the physical aging of PPO membranes was demonstrated by monitoring the time dependence of the permeability and selectivity of the membranes. In general, gas pressure decelerated the physical aging process, especially in earlier stages of the membrane life. Also, the aging of thin membranes is greater than the aging of thick membranes, under all applied gas pressures. In some experiments, anti-trade-off effect, i.e. the decrease in the selectivity together with the decrease in permeability, was observed. A plausible explanation was proposed based on a dual gas permeation model.
Keywords: Engineering, Chemical.